Risk of myocarditis and pericarditis following BNT162b2 and mRNA-1273 COVID-19 vaccination. Issue 35 (19th August 2022) - Goddard, Kristin; Lewis, Ned; Fireman, Bruce; Weintraub, Eric; Shimabukuro, Tom; Zerbo, Ousseny; Boyce, Thomas G.; Oster, Matthew E.; Hanson, Kayla E.; Donahue, James G.; Ross, Pat; Naleway, Allison; et al.
Abstract: Background: Evidence indicates that mRNA COVID-19 vaccination is associated with risk of myocarditis and possibly pericarditis, especially in young males. It is not clear if risk differs between mRNA-1273 versus BNT162b2. We assessed if risk differs using comprehensive health records on a diverse population. Methods: Members 18–39 years of age at eight integrated healthcare-delivery systems were monitored using data updated weekly and supplemented with medical record review of myocarditis and pericarditis cases. Incidence of myocarditis and pericarditis events that occurred among vaccine recipients 0 to 7 days after either dose 1 or 2 of a messenger RNA (mRNA) vaccine was compared with that of vaccinated concurrent comparators who, on the same calendar day, had received their most recent dose 22 to 42 days earlier. Rate ratios (RRs) were estimated by conditional Poisson regression, adjusted for age, sex, race and ethnicity, health plan, and calendar day. Head-to-head comparison directly assessed risk following mRNA-1273 versus BNT162b2 during 0–7 days post-vaccination. Results: From December 14, 2020 – January 15, 2022 there were 41 cases after 2, 891, 498 doses of BNT162b2 and 38 cases after 1, 803, 267 doses of mRNA-1273. Cases had similar demographic and clinical characteristics. Most were hospitalized for ≤1 day; none required intensive care. During days 0–7 after dose 2 of BNT162b2, the incidence was 14.3 (CI: 6.5–34.9) times higher than the comparison interval, amounting to 22.4 excess cases per million doses; after mRNA-1273 the incidence was 18.8 (CI: 6.7–64.9) times higher than the comparison interval, amounting to 31.2 excess cases per million doses. In head-to-head comparisons 0–7 days after either dose, risk was moderately higher after mRNA-1273 than after BNT162b2 (RR: 1.61, CI 1.02–2.54). Conclusions: Both vaccines were associated with increased risk of myocarditis and pericarditis in 18–39-year-olds. Risk estimates were modestly higher after mRNA-1273 than after BNT162b2.